Factors Associated With Sun Protection Behaviors Among Childhood Cancer Survivors. Issue 3 (10th January 2023) - Fluehr, Melissa; Kwok, Gary; Stapleton, Jerod L.; Masterson, Margaret; Devine, Katie A.
Abstract : Background: Childhood cancer survivors (CCS) are at increased risk of developing skin cancer. Engaging in sun-protective behaviors may ameliorate that risk, but prior work shows that survivors engage in suboptimal levels of sun-protective behaviors. Guided by the Health Belief Model (HBM), this study evaluated factors associated with sun-protective behavior among CCS. Methods: This is a secondary analysis of a survey study of 94 adult survivors of childhood cancer recruited from a long-term follow-up clinic. Participants reported their sun protection habits, skin type/sensitivity, barriers to sun protection, and perceived severity and susceptibility of getting skin cancer. Descriptive statistics were used to describe the prevalence of sun protection behaviors and hierarchical linear regression was used to evaluate predictors of sun protection behavior following the HBM. Results: On average, CCS engaged in moderate levels of sun-protective behaviors ( M =2.53; SD=0.59). Hierarchical linear regression indicated that fair skin type ( P =0.02) and higher perceived susceptibility relative to noncancer survivors ( P =0.02) were associated with increased sun protection behaviors. Perceived barriers to sun protection were marginally significant ( P =0.09), whereas other constructs from the HBM did not contribute significantly to the model. Conclusions: Although CCS are at increased risk of developing skin cancer, they engage in suboptimal levels of sun protection behaviors. Findings suggest that interventions to educate survivors about their unique risk of skin cancer and effective prevention behaviors are needed.